Perceived Sources of Stress Among The Students Of a Medical College Of Southern Punjab - Hassan Jan; Fahd Mehtab Ud Din Dogar; Hafiz Ahmed Zeb Khan; Malik Zain Ul Abideen; Malik Saleem Shaukat; Aeeza Malik (Journal of Rawalpindi Medical College)
Objective: To assess the frequency of perceived sources of stress among undergraduate dental students.